Effect of different supplementary feeding methods for breeding efficiency of pigeons - Lengyel, Ármin; Pap, Tibor István; Szabó, Rubina Tünde; Kovács-Weber, Mária (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The aim of our study was to compare different feeding methods and efficiency of feed supplement from commercial trade. The growth and the meat production of nestling homing pigeons (n=78) was measured in three groups and in three brooding periods. 3 to 5-year-old couples and their nestlings were involved in the experiment. In the control group (d0), couples raised the nestlings in traditional way. The d1 experimental group was the drenching group, in the d2 experimental, the feed supplement was added to drinking water of the couple on day 10, 15, 20 and 25. The birds were weighed at the age of 10, 15, 20, 25 and 30 days. The carcase weight was measured on day 30. In the case of brooding periods, there was no significant different between groups in live weight parameter within the following dates: brooding 1: 10, 15, 20 days, brooding 2: 10, 15, 20, 25 days, brooding 3: 20, 25, 30 days. During the brooding 1 and 2 periods, the nestlings of the d2 groups had significantly higher live weight at the age of 30 days compare to the control group. During the early period (10 and 15 days) of brooding 3, d1 group had significantly favourable live weight parameter than d2 group. The beneficial effect of feed supplementation was observed, the d1 and the d2 groups had higher carcase weight compare to the control group. The d2 group had the highest carcase percentages compare to the control and the d1 groups during all three brooding, however these differences were significant only in the brooding 2. Based on our results, the direct feeding (drenching) is recommended, because less attention is given to the older nestlings by parents, it is start growing of the new nest.